Inés Echeverría Bello/Héctor Bello: alter ego y escritura femenina chilena en la tercera parte de la serie histórico/memorialística Alborada (1943-1946) - Arre Marfull, Montserrat Nicole (2020)
From a socio-critical reading, the article proposes the existence of a male alter ego of the female author, as a character from the third part of the Alborada, the historical/memorialistic novels series published by Iris (Inés Echeverría Bello) between 1943-1946 in Chile. From the reading of the three novels in this part of the series, and the author's memoirs, published posthumously, we propose that Iris is introduced into her narrative through the character of “Héctor Bello”, which fulfills the ideological functions that the same author achieved in her political and intellectual space in Chile in the 1910s, however, does not bear the limitations imposed on the elite woman. The use of this alter ego allows the author to legitimize the substantive discussion around the social criticism that she develops, without opening the debate about the freedoms of women in private space so explicitly, and, in this way, maintains a relatively neutral position within the story.